2022
DOI: 10.18502/jmr.v16i2.9305
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Flexion-Relaxation Ratio Symmetry in Subjects with and without Non-Specific Chronic Neck Pain

Abstract: Introduction: Neuromuscular imbalance between right and left sides of Cervical Erector Spinae (CES) muscles can induce pain by applying the asymmetric loads on the spine incorrectly. This study evaluated the symmetry of the right and left cervical flexion-relaxation ratio (FRR) in patients with Non-Specific Chronic Neck Pain (NSCNP) and healthy subjects. We aimed to investigate the symmetry of FRR on the right and left sides of the CES muscles in individuals with and without NSCNP. Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…9 non-english studies were retrieved but not screened due to limited access to translation services [10][11][12][13][14][15][16][17][18]. One study appeared to meet the inclusion criteria but was excluded because we could not con rm it was an independent sample of participants from a previously included study [19]. In total, 55 studies were included in this review, 8 of which assessed multiple measurement properties: 6 reliability (3 lumbar [20][21][22], 3 cervical [23][24][25]), 21 discriminative validity (15 lumbar [21, 22, 26-38], 6 cervical [23,24,[39][40][41][42]), 38 responsiveness (1 thoracic [43], 23 lumbar [30,36,37,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63], 14 cervical [42,…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 non-english studies were retrieved but not screened due to limited access to translation services [10][11][12][13][14][15][16][17][18]. One study appeared to meet the inclusion criteria but was excluded because we could not con rm it was an independent sample of participants from a previously included study [19]. In total, 55 studies were included in this review, 8 of which assessed multiple measurement properties: 6 reliability (3 lumbar [20][21][22], 3 cervical [23][24][25]), 21 discriminative validity (15 lumbar [21, 22, 26-38], 6 cervical [23,24,[39][40][41][42]), 38 responsiveness (1 thoracic [43], 23 lumbar [30,36,37,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63], 14 cervical [42,…”
Section: Study Selectionmentioning
confidence: 99%
“…9 non-English studies were retrieved but not screened due to limited access to translation services 10,[12][13][14][15][16][17][18][19] . One study appeared to meet the inclusion criteria but was excluded because we could not confirm it was an independent sample of participants from a previously included study 20 . 37 studies were found to assume responsiveness but were not designed in a way to measure responsiveness (1 thoracic 21 , 23 lumbar , 14 cervical 41,[45][46][47][48][49][50][51][52][53][54][55][56][57] ).…”
Section: Study Selectionmentioning
confidence: 99%